The choice of optimal drug therapy in patients with atrial fibrillation and comorbid pathology. - Yalovenko, M. I.; Khaniukov, O. O. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Nowadays, atrial fibrillation is considered as a potentially fatal arrhythmia, because of the wide range of its negative outcomes associated not only with a significant deterioration in the patient’s life quality, but also with a significant increase in the rate of fatal complications. Objective. The aim of the work was to determine the effectiveness of drug treatment in patients with persistent atrial fibrillation, hypertension and ischemical heart disease. Methods. The study included 42 patients (mean age - 63.5 ± 2.3; men - 21 (50 %)), with persistent atrial fibrillation, arterial hypertension and chronic ischemic heart disease (stable angina pectoris, classes II-III). All patients had arterial hypertension II-III degree. Patients were divided into groups comparable by age, sex and clinical characteristics. Rivaroxaban 20 mg per day or warfarin (under the control of international normalized ratio), losartan 50-100 mg per day, bisoprolol 5-10 mg per day and atorvastatin - 40 mg per day were administrared to the patient of the main group (n = 21). Nitric oxide donor («Tivortini» 100 ml intravenously) was prescribed in addition to complex therapy. Rivaroxaban at a dose of 20 mg per day or warfarin (under the control of international normalized ratio), ramipril 5-10 mg per day, bisoprolol 5-10 mg per day and atorvastatin - 20 mg per day were administrared to the patient of the control group (n = 21). Results. The use of losartan and ramipril showed the equal antihypertensive effect in patients with atrial fibrillation, ischemic heart disease, and arterial hypertension, which was determined by a significant decrease of systolic and diastolic blood pressure. 19 (90.47 %) patients of losartan group and 17 (80.95 %) - of ramipril one reached the target level of the blood pressure (BP < 140 and 90 mm. hg). A significant improvement in glomerular filtration rate indices and a decrease in uric acid levels were determined in patients treated with losantan. Conclusion. Combination therapy in patients with persistent atrial fibrillation, arterial hypertension and ischemic heart disease consisting of losartan, high doses of atorvastatin and nitric oxide donor contributed to control of the blood pressure, reducing the number and duration of angina attacks, exercise tolerance improving, and also led to a significant decrease in a total cholesterol level, low - density lipoprotein - cholesterol, triglycerides, atherogenic index and uric acid levels.